The Effect of Earning Management and Tax Management on CSR Was Moderated by The Audit Committee - Ajeng Wajayanti; Shiva dewanti Nabil; Alvinania Alvinania (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
This study is a study that examines the effect of Earnings Management and Tax Management on CSR moderated by the Audit Committee. The research method used in this study is a quantitative research method, where the sources are taken from various previous studies and IDX data as many as 10 companies listed in the food and beverage sector. This study finds that (1) Earnings management has a significant effect on CSR with n; (2) Tax Management has a significant effect on CSR; (3) the audit committee is able to moderate the influence of Earnings Management on CSR; (4) the audit committee is not able to moderate the effect of Tax Management on CSR.